Higher Risk for Sjögren’s Syndrome in Patients With Fibromyalgia: A Nationwide Population-Based Cohort Study - Gau, Shuo-Yan; Leong, Pui-Ying; Lin, Cheng-Li; Tsou, Hsi-Kai; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Abstract Objectives Clinically, associations have been observed between Sjögren’s syndrome and fibromyalgia. Nonetheless, population-based evidence evaluating the risk of Sjögren’s syndrome in fibromyalgia patients is lacking. The main purpose of this retrospective cohort study was to determine the association between fibromyalgia and subsequent development of Sjögren’s syndrome. Methods This retrospective cohort study extracted data from the Longitudinal Health Insurance Database (LHID) of the Taiwan National Health Insurance (NHI). During 2000-2012, patients with newly-diagnosed fibromyalgia (International Classification of Diseases, Ninth Revision, Clinical Modification code 729.1) were defined as the exposure cohort. Age- and gender-matched individuals without fibromyalgia were used as the comparison cohort. The adjusted hazard ratios (aHR) for the occurrence of Sjögren’s syndrome in those with fibromyalgia were evaluated along with stratified analyses of different subgroups. Results Of the 149,706 subjects whose data were extracted from the LHID, 74,853 subjects had coded fibromyalgia and 74,853 control subjects were without fibromyalgia. Compared to the control group, patients with fibromyalgia had an aHR of 2.00 (95% Confidence Interval [CI], 1.52-2.61) for developing Sjögren’s syndrome. In fibromyalgia patients aged 20-49 years, the aHR for future Sjögren’s syndrome was 3.07 (95% CI, 1.92-4.89). Conclusion Patients with fibromyalgia, both males and females, have a higher risk for developing Sjögren’s syndrome than those without fibromyalgia, especially those aged 20-49 years. While managing patients, clinicians should be aware of the bidirectional association between the two diseases, which helps to understand the impact of the association on disease activity and diagnosis.